Towards sustainable conversation: Developing environmental education processes - Kim le Roux (Environmental Association of Southern Africa, 1997)
This paper highlights the importance of seeing environmental education as a process and considers the value of conversation and storytelling in environmental education processes. These processes are explored from a post-structural perspective within the context of the writer's own involvement in supporting environmental education processes.